Role of Neuroactive Steroids in the Peripheral Nervous System - Melcangi, Roberto Cosimo; Giatti, Silvia; Pesaresi, Marzia; Carabrese, Donato; Mitro, Nico; Caruso, Donatella; Garcia-Segura, Luis M. (Frontiers in Endocrinology, 2011)
Several reviews have so far pointed out on the relevant physiological and pharmacological role exerted by neuroactive steroids in the central nervous system. In the present review we summarize observations indicating that synthesis and metabolism of neuroactive steroids also occur in the peripheral nerves. Interestingly, peripheral nervous system is also a target of their action. Indeed, as here reported neuroactive steroids are physiological regulators of peripheral nerve functions and they may also represent interesting therapeutic tools for different types of peripheral neuropathy.